Zur Entwicklung der Sparquoten der privaten Haushalte: eine Auswertung von Haushaltsdaten des SOEP - Ulrike Stein (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
– According to the National Accounts the German savings rate has increased continuously since 2001 after it fell continuously from 1991. This increase was rather unexpected and hence it is interesting to analyse whether the savings rate of the total population has increased or whether the increase in the aggregated savings rate has been due to the fact that the savings behaviour of certain socio-economic groups developed differently during the last decade. For this project data from the German Socio-Economic Panel (SOEP) is used for the years 1995 to 2007. The analysis of household's savings rates differentiated according to socio-economic characteristicsshows, that the savings rates develop differently depending on the respective householder's labour market status. The examination of savings rates of different age groups does not provide conclusive results. Finally, the increase in the aggregate savings rate is attributed alone to the changed savings behaviour of the households in the top quartile of the income distribution whereas the savings rates of the other quartiles tend to have declined.
Keywords: E21; H31; 330; Sparquoten; Haushalte; Sozioökonomische Gruppen; SOEP